Electrosynthesis of Sodium Hypochlorite Using Ion Exchange Membrane - Juan T. Medina Collana; Carlos A. Ancieta Dextre; Oscar J. Rodriguez Taranco; Kevin R. Azorza Guillen; Cynthia L. Roca Pelayo; Denis Gabriel Hurtado; David Mitma Ramirez; Santos P. Alvarez López (Chemical Engineering Transactions)
In this article, we report on a newly designed insitu sodium hypochlorite generation process at laboratory scale. An anion exchange membrane was placed between two cation exchange membranes, dividing the cell into distinct compartments. The factorial design comprised three level variations for sodium chloride concentration as well as for electrical potential on the effect of sodium hypochlorite concentration and specific energy consumption. The most favorable operating conditions gave a concentration of 1800 mg/L of NaClO with a solution of 20 g/L NaCl and a voltage of 15 volts. The findings indicate an energy expenditure between (8.13 to 35.68 kWh/kg NaClO) associated with the production of a concentration between(906.9-1800 mg/L) of sodium hypochlorite . Based on the results achieved, it is possible to build an electrolyzer with an ion exchange membrane to obtain a sodium hypochlorite solution from low concentration sodium chloride.